Parental Support for Speech Delay in Early Childhood in Kalisari Village, Natar District, South Lampung Regency - Anggraini, Hetty; Ramadhani, Nurul (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
This study was aims to explore, describe, and analyze parent support for the speech delay early childhood. This study used to the qualitative method of the research subject is both parents of children who experience speech delay in Kalisari village. This study was used to three methods of data collection, namely observation, interviews, and documentation. The data analyze used to descriptive qualitative. Based on the results of the discussion that has been described it can be concluded that parent support that has been given to children who experience speech delay is informational support, assessment support, instrumental support, emotional social support, and real support. Of the five supports, the researchers concluded that the support often used by subjects was informational support, namely parents provided support through the provision of good advice and advice, giving instructions by installing pictures in the refrigerator so that the twins could understand the food taken and want to say food they took, and provided information by taking the twins for a walk to get a new vocabulary.